PENDEKATAN PER SE ILLEGAL DALAM PERJANJIAN PENETAPAN HARGA (PRICE FIXING) TERKAIT KASUS PT. EXCELCOMINDO PRATAMA, Tbk. - Mery Astuti, Ni Ayu Putu; Wiryawan, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015)
This paper is titled Per Se Illegal Approach on Price Fixing Agreement with Regard to PT. Excelcomindo Pratama, Tbk., Case. The purpose of this paper is to know that the price fixing as an illegal agreement in a business world and the outcome of PT. Excelcomindo Pratama, Tbk., case. This paper using juridical-empirical research method with statute approach, case approach, and historical approach. This paper discusses price fixing, per se illegal approach, and the outcome of PT. Excelcomindo Pratama, Tbk., case. In which the fixing price agreement as was conducted by PT. Exclcomindo Pratama, Tbk., is per se illegal or absulutely not allowed because of its anti-competition nature, and almost never bring any social benefits.
Keywords: Agreement, Price Fixing, Per Se Illegal